The Effect of Capital Structure, Leverage, and Firm Size on Financial Performance of Basic Materials Sector Companies Listed on the Indonesia Stock Exchange - Yuliasih Triska Sugiarti; Heru Cahyo; Endang Sri Wahyuningsih (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
Financial performance is a critical indicator of a company’s ability to manage resources effectively and achieve sustainable business objectives. In the basic materials sector, companies face challenges related to commodity price fluctuations, economic uncertainty, and post-pandemic pressures that may affect their financial performance. This study aimed to examine the effects of capital structure, leverage, and firm size on the financial performance of basic materials companies listed on the Indonesia Stock Exchange during the 2019–2024 period. A quantitative approach was employed using secondary data obtained from companies’ annual financial statements. The sample consisted of 24 companies selected through purposive sampling. Data were analyzed using panel data regression with the Fixed Effect Model (FEM). The findings reveal that capital structure, measured by the Debt to Equity Ratio (DER), has a negative and significant effect on financial performance. Leverage, measured by the Debt to Assets Ratio (DAR), has a positive and significant effect on financial performance, whereas firm size does not have a significant effect. The study concludes that financing structure and debt management are more decisive in shaping financial performance than organizational scale. These findings contribute to corporate finance literature by providing sector-specific evidence on the determinants of financial performance in Indonesia’s basic materials sector. Practically, the study implies that companies should formulate optimal financing policies and allocate debt productively to enhance profitability and support long-term business sustainability.